SEDIMENT STRATIGRAPHY IN DUMAI WATERS RIAU PROVINCE - Hutasoit, Ramot S; Ghalib, Musrifin; ', Rifardi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in February 2016 in Dumai Waters, aimed to knows an illustration of sediment texture changes vertically in Dumai Waters. Sediments sample was collected by gravity core. Each sample collected was divided into 26 and 27 layers at 1 cm dense, therefore samples amount were 53 samples. Data was analyzed descriptively and was processed with cluster analysis. Based on the results, it was concluded that sediment type in Dumai Waters were categorized into fine sand,very fine sand, coarse silt, medium silt and fine silt. Cluster analysis showed of six groups sediment in research station. In station II all cluster group were found, while in station I only four were found. Each layer of different cluster showed diversity of sediment characteristic. This illustration indicated that difference of sedimentation process which caused by difference of waters condition from time to time.Keywords: Stratigraphy, Sedimentation, Characteristic, Cluster, Dumai Waters